Coincidence point theorems for geraghty’s type contraction in generalized metric spaces endowed with a directed graph - Narawadee Phudolsitthiphat (2019)
© 2019 by the Mathematical Association of Thailand. All rights reserved. In this work, we present some existence results for coincidence point theorems for Geraghty’s type contraction mappings in a space with two generalized metrics endowed with a directed graph. Further, some examples are provided to support our main theorems. Finally, these results can be applied to the integral equation.